Nosocomial infections after acupuncture and related therapies: A systematic review of case reports and case series - Chao-Yue ZHANG; Jun XU; Xiao-Hong GU; Xuan YIN; Shan-Shan LI, (李珊珊); Li-Xing LAO; Shi-Fen XU; Yi-Qun MI (World Journal of Acupuncture - Moxibustion)
Background: Acupuncture and its related therapies, as an important part of traditional Chinese medicine, have been widely accepted by the public and healthcare professionals all over the world. According to previous reviews, the department of acupuncture is a potential place where nosocomial infection might occur. Objectives: To investigate the common pathogens and possible risk factors for nosocomial infection, figure out the measures and strategies for control and prevention, and provide general reporting guideline for future cases. Methods: A systematic literature search of 6 libraries (EMBASE, CINAHL, PubMed, VIP, CNKI, SinoMed) was carried out on nosocomial infection (NIs) after acupuncture and its related therapies (e.g., moxibustion, cupping, massage, dry needling) published from January 1, 2012 to August 31, 2023. Studies providing primary data were included; reviews, comments, and non-primary data studies were excluded to prevent duplicate case analysis. Data on bibliographic details, study characteristics, and clinical information were extracted. Results were synthesized through tabulation and categorized by therapy type, country income level, symptoms/diagnoses, pathogens, risk factors, treatments, and outcomes. Conclusion: Nosocomial infections after acupuncture and its related therapies are possible but preventable. Prevention measures can be carried out in terms of the risk factors listed above. Future case reports are suggested to provide specific details of infection, including the setting, qualification, treatment, disinfection, and causal evidence.